Before and after out-of-home placement: Child health, education and crime - Petra Gram Cavalca; Mette Ejrnæs; Mette Gørtz (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2022)
We investigate the short-term impact of out-of-home care on child health, schooling and juvenile crime. Using an event study to examine the dynamics around the time of placement, we document a clear deterioration of mental health and increasing crime rates before placement. After placement, we find a decrease in hospitalizations and an improvement in schooling outcomes. For a sub-sample, we use caseworkers' risk-assessment to form a control group of children who were at risk of a placement. For the marginal child, we find little evidence of a causal effect of placement, as we also see improvements for the control group.
Keywords: H75; I14; I21; I38; J12; J13; 330; Child protection; health; schooling; crime; event study